Gender Difference in the Characteristics among Unintentional Methamphetamine Overdose Patients Referring to Poison Center-an Epidemiologic Survey - Khodabandeh, F (International Journal of Medical Toxicology and Forensic Medicine, 2013)
<!–[if gte mso 9]> <![endif]–> Background: Despite a significant increase in the number of persons using Methamphetamine, limited data exist concerning demographic characteristics non-fatal meth ”Shisha” overdoses, seeking for treatment. Methods: Gender differences in socio-demographic characteristics, drug use record and self-harm behaviors related to Methamphetamine “Shisha” overdose were examined among 263 patients (189males, 74 females) admitted to poison center, Loghman hospital. Results: Of the 263 methamphetamine “Shisha” overdose included in this study, 189 (71.9%) were Male and 74 (28.1%) were female with mean of age of 34 years and standard deviation of 12.8. Male “Shisha” users were more likely to be married, middle school educated, and self-employed. History of drug abuse was positive in 73.5% mainly in male. “Shisha” was the main drug used by 24.6% male and 23.1% female subjects. Inhalation was main rout in 174 (66.2%) of cases. Conclusion: There may be gender difference in the characteristics of participants with “Shisha” overdose. The findings suggest that interventional programs are necessary for specific risk reduction strategies.